2010
DOI: 10.1111/j.1742-1241.2010.02347.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Humalog Mix 50 with human insulin Mix 30 in type 2 diabetes patients during Ramadan

Abstract: Changing to humalog Mix 50 during Ramadan resulted in improvement in glycaemic control without increasing the incidence of hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…18 In another study, switching from premixed insulin formulation (30% regular/70% NPH) to 50 regular/50NPH insulin during the evening meal demonstrated a reduction in HbA1c with less hypoglycemic episodes. 19 The use of insulin pump therapy has been shown to be effective in improving glycemic control and in reducing the risk of hypoglycemia in patients with type 1 diabetes during Ramadan. The use of an insulin pump helps to provide a continuous basal rate of insulin during the fasting period and to rapidly cover for meals intake after the breaking of the fast.…”
Section: Use Of Glucose-lowering Medications During Ramadanmentioning
confidence: 99%
“…18 In another study, switching from premixed insulin formulation (30% regular/70% NPH) to 50 regular/50NPH insulin during the evening meal demonstrated a reduction in HbA1c with less hypoglycemic episodes. 19 The use of insulin pump therapy has been shown to be effective in improving glycemic control and in reducing the risk of hypoglycemia in patients with type 1 diabetes during Ramadan. The use of an insulin pump helps to provide a continuous basal rate of insulin during the fasting period and to rapidly cover for meals intake after the breaking of the fast.…”
Section: Use Of Glucose-lowering Medications During Ramadanmentioning
confidence: 99%
“…Similarly, in another study insulin lispro Mix50 (50% lispro/50% lispro protamine) in the evening and regular human insulin with NPH (30:70) in the morning improved glycaemic control without increasing the incidence of hypoglycaemic events compared with regular human insulin with NPH (30:70) given twice daily [55].…”
Section: Insulin Treatment For T2dmmentioning
confidence: 99%
“…27 However, the findings of an observational study suggested that using Humalog Mix50 (Lilly) at ifta instead of Mix30 reduced postprandial glucose excursions and reduced hypoglycaemia. 28 We suggest that patients taking twice daily insulin should reduce the suhur dose by 30% if they are well controlled, and consider switching to a Mix 50 preparation if their postprandial glucose remains raised.…”
Section: Premixed Insulinsmentioning
confidence: 99%